Necrobiosis Lipoidica following Breast Reduction. Issue 9 (13th September 2021) - Absil, Gilles; Collins, Patrick; El Hayderi, Lara; Nikkels, Arjen F.
Abstract : Summary: Necrobiosis lipoidica (NL) is a rare granulomatous skin disorder of unknown physiopathology that is frequently associated with diabetes mellitus. The typical skin lesions of NL present as chronic, bilateral, well-defined red to yellow-brown plaques with telangectasias, a violaceous border and a waxy atrophic center. The lower legs are the most often involved areas, but NL may exceptionally develop on scar tissue following surgery. The treatment is very challenging and notoriously difficult. We report a 60-year-old diabetic woman who developed NL all along the surgical scars following breast reduction, without presenting NL on the lower legs. NL should be considered among the rare but possible skin healing complications of surgery.